Preparation of TiO2 nanotube on glass by anodization of Ti films at room temperature - 汤育欣 陶杰 张焱焱 吴涛 陶海军 朱亚蓉 (Transactions of Nonferrous Metals Society of China, 2009)
In order to fabricate titania nanotubes on glass substrate, Ti thin fihns （700-900 nm） were first deposited by radio-frequency（RF） magnetron sputtering and then anodized in an aqueous HF electrolyte solution at room temperature. The morphology and structure of the nanotubes were identified by means of field emission scanning electron microscopy（FE-SEM） and X-ray diffractometry（XRD）. The effects of anodization parameters （concentration of electrolyte, applied voltage） on nanotube morphology were comprehensively investigated. The results show that the dense and crystalline Ti film can be obtained on the unheated glass substrate under the sputtering power of 150 W, and the anodization current and voltage play significant roles in the formation of titania nanotube with different tube sizes.